2017
DOI: 10.9746/jcmsi.10.125
|View full text |Cite
|
Sign up to set email alerts
|

Extended High-Gain Observers as Disturbance Estimators

Abstract: : This paper reviews recent results on the use of extended high-gain observers as disturbance estimators. It shows how the use of these observers enables recovering the performance of feedback linearization controllers. It shows also how the observer can be combined with dynamic inversion. Three experimental applications are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Authors in Reference [44] proposed a MIMO nonlinear anti-disturbance compensator based on the linear extended state observer (LESO) for an unmanned aerial vehicle with exogenous disturbances and uncertainties. Authors in Reference [45] demonstrated an extended high-grain observer as a disturbance estimator in combination with a dynamic inversion technique with an application on nonlinear MIMO systems.…”
Section: Related Workmentioning
confidence: 99%
“…Authors in Reference [44] proposed a MIMO nonlinear anti-disturbance compensator based on the linear extended state observer (LESO) for an unmanned aerial vehicle with exogenous disturbances and uncertainties. Authors in Reference [45] demonstrated an extended high-grain observer as a disturbance estimator in combination with a dynamic inversion technique with an application on nonlinear MIMO systems.…”
Section: Related Workmentioning
confidence: 99%
“…Inspired by classical approaches in output feedback literature, we propose a simple paradigm composed of two steps. First, we design an extended high-gain observer [8,16,25] able to recover the input y from the filter (3). Then, we replace the input of the controller (2) by the saturated version of the estimate given by the observer.…”
Section: Assumptionmentioning
confidence: 99%
“…For this, the full knowledge of the state x of the plant Σ is not required. To this end, the main idea is to use a disturbance observer [8] designed in particular as an extended high-gain observer (see, e.g., [16,25], also known as extended state observer, [20]) able to recover the output y of Σ from the estimation of the state of the filter Σ f . In the same spirit of standard results about separation principle for nonlinear systems in semi-global output feedback stabilization (see, e.g., [4,29,30]), the resulting controller allows to stabilize an equilibrium of the cascade system Σ-Σ f with a domain of attraction that includes the set of initial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [27] suggested a new fractional decentralized control for aircraft engines, which are considered as uncertain large-scale systems composed of interconnected uncertain subsystems. Finally, the authors in [28] validated a dynamic inversion technique in combination with a disturbance estimator and applied it to MIMO nonlinear systems.…”
Section: Introductionmentioning
confidence: 99%